Osteopontin inhibits osteoblast responsiveness through the down-regulation of focal adhesion kinase mediated by the induction of low–molecular weight protein tyrosine phosphatase - Kusuyama, Joji; Bandow, Kenjiro; Ohnishi, Tomokazu; Hisadome, Mitsuhiro; Shima, Kaori; Semba, Ichiro; Matsuguchi, Tetsuya (Molecular biology of the cell, 2017)
Osteopontin (OPN) is an osteogenic marker protein. Osteoblast functions are affected by inflammatory cytokines and pathological conditions. OPN is highly expressed in bone lesions such as those in rheumatoid arthritis. However, local regulatory effects of OPN on osteoblasts remain ambiguous. Here we examined how OPN influences osteoblast responses to mechanical stress and growth factors. Expression of NO synthase 1 (Nos1) and Nos2 was increased by low-intensity pulsed ultrasound (LIPUS) in MC3T3-E1 cells and primary osteoblasts. The increase of Nos1/2 expression was abrogated by both exogenous OPN overexpression and recombinant OPN treatment, whereas it was promoted by OPN-specific siRNA and OPN antibody. Moreover, LIPUS-induced phosphorylation of focal adhesion kinase (FAK), a crucial regulator of mechanoresponses, was down-regulated by OPN treatments. OPN also attenuated hepatocyte growth factor–induced vitamin D receptor (Vdr) expression and platelet-derived growth factor–induced cell mobility through the repression of FAK activity. Of note, the expression of low–molecular weight protein tyrosine phosphatase (LMW-PTP), a FAK phosphatase, was increased in both OPN-treated and differentiated osteoblasts. CD44 was a specific OPN receptor for LWW-PTP induction. Consistently, the suppressive influence of OPN on osteoblast responsiveness was abrogated by LMW-PTP knockdown. Taken together, these results reveal novel functions of OPN in osteoblast physiology.